Complementary molecular and visual sampling of fish on oil and gas platforms provides superior biodiversity characterisation. (July 2022) - Alexander, Jason B.; Marnane, Michael J.; Elsdon, Travis S.; Bunce, Michael; Songploy, Se; Sitaworawet, Paweena; Harvey, Euan S.
Abstract: Offshore oil and gas platforms have the potential to provide complex refugia for fish and benthic colonisers. We compare two methods of biodiversity assessment for fish and elasmobranchs at seven decommissioned oil and gas platforms as well as five sediment sites, located 5 km from platforms, in the Gulf of Thailand. Using surveys from stereo-video ROV transects, and data from Environmental DNA (eDNA) water-column samples, we detected fish and elasmobranch taxa from 39 families and 66 genera across both platform and sediment sites with eDNA, compared with 18 families and 29 genera by stereo-ROV with platforms yielding significantly greater species richness. This study demonstrates that the combination of stereo-video ROV and eDNA provide effective, non-extractive and complementary methods to enhance data capture. This approach sets new benchmarks for evaluating fish assemblages surrounding platforms and will enhance measurements of biota to inform decisions on the fate of oil/gas infrastructure. Highlights: EDNA and stereo-ROV methods detected 41 families and 69 genera from platforms. Detection composition varied with 10 families detected with both methods. Platform locations significantly more diverse than sediment locations. EDNA detected greater numbers of reef-associated species at sediment sites. Combined methodologies can reduce biases involved with individual method detections.